The moderating effect of job satisfaction on the relationship between human capital dimensions and internal audit effectiveness - Mohannad Obeid Al Shbail; Hashem Alshurafat; Husam Ananzeh; Tareq O Bani-Khalid (Cogent Business & Management, 2022)
This study examined how job satisfaction affected the link between internal audit effectiveness and human capital dimensions in the context of Jordanian commercial banks. In this paper, from the distributed questionnaire copies distributed to internal auditors working in the commercial banks of Jordan, 102 copies were deemed useable. Data obtained was exposed to Partial Least Squares-Structural Equation Modeling (PLS-SEM). Based on the results, education, expertise, and training had a direct, positive, and significant influence on the effectiveness of internal audit, while job satisfaction had an incomplete role as a moderator, as underpinned by the Social Exchange theory. The study enumerates the implications for practice and academics, with the study contributions serving as guidelines for bank managers and literature research. On this basis, the study implications are categorized into two major types, theoretical and practical implications. Accordingly, the first contribution to theory is that social exchange theory adoption to examine the human capital dimensions (education, expertise, and training) and their relationship with internal audit effectiveness. Also, practically, the study findings indicate the strategic importance of internal audit, reminding executives and banks directors to enhance internal audit staff expertise and meet their satisfaction to promote the effectiveness of the internal audit.
Keywords: 650; Human Capital; Internal Audit Effectiveness; Job SATISFACTION; Partial Least Squares-Structural Equation Modeling (PLS-SEM)